PROSTITUSI ONLINE DALAM PERSPEKTIF HUKUM PIDANA DI INDONESIA - Faturohman Faturohman (Res Justitia : Jurnal Ilmu Hukum, 2022)
The life of modern man today cannot be separated from the internet network. Because, the internet is a network system that can connect one device to another. The Internet cannot be separated from human life today, and almost all humans in parts of the world depend on the internet network. The existence of the Internet network has a positive impact, especially making it easier for someone to be able to access all kinds of needs. There is ease in making transactions using the internet network, it is actually used by criminals as a means to commit crimes, one of which is used as an online prostitution service. Technological and industrial advances that are the result of human culture in addition to bringing positive impacts, in the sense that they can be used for the benefit of mankind also have a negative impact on the development and civilization of human beings themselves. The negative impact in question is related to the world of evil. Prostitution is not a new problem. This problem of prostitution has existed for a long time and until now it still cannot be resolved. Prostitution is a serious matter that must get more attention by the public and the government. Prostitution in Indonesia is considered a crime against decency and is illegal and contrary to human rights. The practice of prostitution is an activity that should be stopped or prohibited because it is considered contrary to religious values and decency. Criminal law in Indonesia does not clearly prohibit the act of prostitution as a form of criminal act. Criminal law has not been able to cover this issue of prostitution. In the Criminal Code we can only find Articles that can ensnare muncikari only as stipulated in Article 296 of the Criminal Code and Article 506 of the Criminal Code